Letramento em saúde e compreensão do termo de consentimento livre esclarecido em pesquisa clínica - Amorim, Renée Costa (2022)
Researches are very important for the development and evolution of science, but it is necessary to respect the decision-making autonomy of the human being. The Informed Consent Form (ICF) arised in response to the atrocities that occurred in World War II, and in Brazil with the Resolution of the National Health Council (NHC) 196/96. Functional Health Literacy (FHL) is the ability to obtain, process and understand basic information and services in order to make appropriate decisions about health and care. This study aimed to analyze the FHL test applied to 40 clinical research participants, considering the understanding of the ICF, and to verify the FHL of clinical research participants at Santa Casa de Votuporanga Hospital. This is an observational, transversal, descriptive research with a quantitative approach. To assess the understanding of the ICF, a questionnaire containing sociodemographic characteristics and questions related to the ICF itself was used, based on what is recommended by Resolution CNS 466/12. To assess the FHL, the B-THOFLA (Brief Test of Functional Health Literary in Adults) questionnaire was used, validated for Brazilian Portuguese. No procedure started before approval by the Research Ethics Committee. Information about research participants was coded and anonymously stored in an Excel® database and statistical analyzes were performed using the Stata® software, version 15.1. Significant ssociations with p value < 0.05 were statistically considered. The 40 study participants were evenly distributed between men and women, with a mean age of 65.5 years old. 40% of the participants reported not knowing what the Informed Consent Form was. 19 people reported that they signed the ICF without reading it and 14 people partially read the content. Also, 12 people were unable to inform whether the study had a placebo, and 60% of participants did not clearly know what a placebo was. The majority (77.5%) did not know how long the study would last, 6 people did not know they could stop the study and the same number of individuals reported that not participating in the study implied the cessation of treatment. The level of education brings one of the main analysis components of the study, which is the low education level of the research participants, since 55% of them had only incomplete elementary education. Using an adjusted linear regression model, we identified that gender, age and education were associated with the mean variation of the total FHL test score, with women and more educated people having higher scores and increasing age was associated with a decrease in the mean score, with R² of the final model of 0.57. More studies must be carried out in order to spread a culture of respect for norms so that human dignity is preserved and patients participate in research in an autonomous and enlightened way. Although with some limitations, our study could contribute to the understanding of researchers in Brazil that health and education actions targeted to research participants are tools for empowerment, decision-making autonomy and respect for research ethics